Physicochemical modulation of chitosan‐based hydrogels induces different biological responses: Interest for tissue engineering. Issue 10 (30th November 2013) - Rami, Lila; Malaise, Sebastien; Delmond, Samantha; Fricain, Jean‐Christophe; Siadous, Robin; Schlaubitz, Silke; Laurichesse, Eric; Amédée, Joëlle; Montembault, Alexandra; David, Laurent; Bordenave, Laurence
Abstract Polysaccharide‐based hydrogels are remarkable materials for the development of tissue engineering strategies as they meet several critical requirements for such applications and they may partly mimic the extracellular matrix. Chitosan is widely envisioned as hydrogel in biomedical fields for its bioresorbability, biocompatibility, and fungistatic and bacteriostatic properties. In this study, we report that the modulation of the polymer concentration, the degree of acetylation, the gelation processes [or neutralization routes (NR)] in the preparation of different chitosan‐based hydrogels lead to substantially and significantly different biological responses. We show that it is possible to tune the physicochemical characteristics, mechanical properties, and biological responses of such matrices. Physical hydrogels prepared from highly acetylated chitosan were softer, degraded quickly in vivo, and were not suitable for in vitro culture of human mesenchymal stem and progenitor derived endothelial cells. In contrast, for a same chitosan concentration and obtained by the same processing route, a low degree of acetylation chitosan hydrogel provided a more elastic material, better cell adhesion on its surface and tissue regeneration, and restored tissue neo‐vascularization as well. This work offers promising and innovative perspectives for the design of hydrogel materials with tunable properties for tissue engineering and regenerative medicine. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3666–3676, 2014.